The role of village community empowerment institution in Galanti village development of Buton district - Indah Kusuma Dewi (Lembaga Penelitian dan Pengabdian Masyarakat, 2019)
The village plays an important role in national development not only because most of the people of Indonesia reside in the village, but the village contributes greatly in creating national stability. The purpose of this study was to determine how the role of social institutions and to find out what factors hampered the role of social institutions in developing Galanti Village. The method in this study is juridical empirical, which clearly distinguishes facts from norms, views legal phenomena must be purely empirical, namely social facts, using empirical science methods (qualitative methods or quantitative methods and value-free. The results of the study indicate that the development of villages in Galanti Village can run well according to the Village Medium Term Development Plan. As for the factors that hamper the role of the Galanti Village Community Empowerment Institution is the lack of human resources in developing productive businesses, the lack of knowledge of business groups that have formed in the villages in developing his group's activities and lack of understanding in carrying out their tasks and functions, besides the lack of public knowledge in utilizing various potential local economic development as an alternative effort to increase their income and welfare.